Professor Develops Musical Robot. (Computer (00189162), 2006)
The article provides information about Haile, a drummer robot invented by Professor Gil Weinberg of Georgia Institute of Technology, Atlanta, Georgia. Haile, which was named after Emperor Haile Selassie of Ethiopia, can play drums with humans and has listening and analytical capabilities. Users control Haile through an Apple iBook which communicates with other elements via an Ethernet board. According to Weinberg, Haile is designed to combine the benefits of computational power, perceptual modeling, and algorithmic music with the richness and expression of acoustic play.